2004
DOI: 10.1515/znc-2004-11-1215
|View full text |Cite
|
Sign up to set email alerts
|

Role of Salicylic Acid in Tomato Defense against Cotton Bollworm, Helicoverpa armigera Hubner

Abstract: We investigated the role of the salicylic acid (SA) signaling pathway in defense responses of tomato plants to the herbivore, cotton bollworm. After exposure to the cotton bollworm, tomato leaves rapidly accumulated a high level of SA. The transcription of PR1 and BGL2 genes, the marker genes of SA pathway, was up-regulated. An enhanced endogenous SA level was accompanied by an increase in the endogenous H2O2 level as compared with controls. Spraying tomato plants with a solution containing either SA or methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 1 publication
2
39
0
2
Order By: Relevance
“…Production of ROS by SA pathway has been proposed to induce resistance in plants against insect pests, e.g., in tomato plants against H. armigera. 135 H 2 O 2 induced by SA in plants defends them against various insect pests since H 2 O 2 actively damages the digestive system of insects leading to reduced growth and development. 35,135 Furthermore, SA signals the release of plant volatiles that attract the natural enemies of insect pests, e.g., Lima bean and tomato plants infested by spider mite attract the natural enemies of spider mite.…”
Section: Role Of Reactive Oxygen Species (Ros) In Plant Defensementioning
confidence: 99%
See 1 more Smart Citation
“…Production of ROS by SA pathway has been proposed to induce resistance in plants against insect pests, e.g., in tomato plants against H. armigera. 135 H 2 O 2 induced by SA in plants defends them against various insect pests since H 2 O 2 actively damages the digestive system of insects leading to reduced growth and development. 35,135 Furthermore, SA signals the release of plant volatiles that attract the natural enemies of insect pests, e.g., Lima bean and tomato plants infested by spider mite attract the natural enemies of spider mite.…”
Section: Role Of Reactive Oxygen Species (Ros) In Plant Defensementioning
confidence: 99%
“…135 H 2 O 2 induced by SA in plants defends them against various insect pests since H 2 O 2 actively damages the digestive system of insects leading to reduced growth and development. 35,135 Furthermore, SA signals the release of plant volatiles that attract the natural enemies of insect pests, e.g., Lima bean and tomato plants infested by spider mite attract the natural enemies of spider mite. 97 However, it has been reported that SA and JA act antagonistically, where SA inhibits the activity of JA and vice versa.…”
Section: Role Of Reactive Oxygen Species (Ros) In Plant Defensementioning
confidence: 99%
“…2,3,19 Elicitors such as jasmonic acid, SA and ethylene have been found to induce such enzymes in plants. [2][3][4][5][6][7][8][9][10][11] Induction of these enzymes by exogenous application of SA and their role in plant defense against various stresses including salinity, 10 drought, 21 pathogens, 4,22 and insects, 8,20,23 has been studied in many plants.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Interestingly, many induced defenses are found not only in damaged local leaves but also in undamaged systemic tissues located distal to the attack sites (van Dam et al, 2001;Schilmiller and Howe, 2005;Wasternack et al, 2006), thus allowing the plant also to cope with highly mobile herbivores. Many plant hormones are involved in these responses, including jasmonates, salicylates, and ethylene (Kahl et al, 2000;Ziegler et al, 2001;Peng et al, 2004;Halitschke and Baldwin, 2005;von Dahl et al, 2007). Among these, the jasmonate-signaling pathway plays a central role.…”
mentioning
confidence: 99%